Personal genomics and personalized medicine - Bolouri, Hamid (London, England : Imperial College Press ; Singapore ; Hackensack, New Jersey : Distributed by World Scientific Publishing, 2010)
Provides a scientific treatment of the disciplines of personal genomics and personalized medicine. This book includes a comprehensive treatment of both the promises and challenges of personal genomics and medicine from technological, societal and medical perspectives. It is suitable for practicing health professionals and researchers.
1. Introduction -- 2. From DNA sequence to physiology -- 3. DNA sequence variations, their prevalence, and effects on cellular biochemistry -- 4. Environmental and life-history effects -- 5. The impact of inter-individual biochemical differences on health outcomes -- 6. DNA testing and sequencing technologies -- 7. Measuring the impact of environmental factors on health -- 8. Characterizing the effects of genetic and environmental factors on cellular function -- 9. Translating personal genomics and personalized medicine into clinical practice -- 10. Organizational, legal and ethical challenges -- 11. Coda : engineering the future of medicine
Includes bibliographical references and index
Keywords: Genomics; Medical genetics; Proteomics; Genetics, Medical; Genomics; Proteomics